The Correlation Between the Smartphone Addiction and Eating Behaviour of Adolescents in Lampung Province - Sugeng Eko Irianto; Biyanti Lisatriana; Nurulita Tunjungsari; Tubagus Erwin Nurdiansyah (Indonesian Journal of Global Health Research, 2021)
Adolescents are those of the Generation Z who are now between 11-26 years old. Adolescents is also called the generation of Internet, who are those who have been familiar with and introduced to the technology and connected to the Internet ever since they were born. In result, Internet has a big impact to the life development and the character building of adolescents. The objective of the study was to discover the correlation between the smartphone addiction and eating behaviour of adolescents in Lampung Province. This is a quantitative analytic study with an observational research design and cross-sectional approach. This research was conducted between September – October 2021 in Lampung Province. The most respondent age was > 17 years or 66.8 % and female was 366 respondent or 73.2%. The respondent who had smartphone addiction level of moderate and severe was 251 respondents or 50.2 %. The eating behaviour of less healthy was 251 respondents or 50.2 % and health eating behaviour was 249 respondents or 49.8%. There was no significant correlation between the adolescent age group and eating behavior (p-value = 0.543). There was a significant correlation between adolescent sex and eating behavior (p-value = 0.001). There was a significant relationship between smartphone addiction and eating behavior in adolescents (p-value = 0.0005). Need further research of the correlation between smartphone addiction with eating behaviour and health.